Promoting Reflective Journal as an Approach to Enhancing EFL Students’ Writing Skills - effi wahyuningsih (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
This study aims at improving the students’ writing skills through promoting reflective journal writing. This is a classroom action research. The data were gained through observation, questionnaire, interview, written testimonies, and writing tests. The research findings reveal that reflective journal writing promotes the students to get progress in their writing skills achieved through some indicators shown in each meeting. They cover the improvement of a) the mean score of each writing component affecting the increase of the mean score of the students' writing tests, b) the scoring category from